Fluorescent theranostic agents for Hg2+ detection and detoxification treatment1. Issue 21 (14th March 2015) - Song, Chao; Yang, Wen; Zhou, Nannan; Qian, Rui; Zhang, Yajun; Lou, Kaiyan; Wang, Rui; Wang, Wei
<x xml:space="preserve">Abstract</x> Two novel small-molecule based theranostic agents encompassing the dual functions of detection and detoxification of mercury ion poisoning are developed.